Separately $Fσ$-measurable functions are close to functions of the first baire class - Banakh, T. O.; Vovk, M. I. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We prove that a Borel separately $Fσ$-measurable function $f: X × Y → R$ on the product of Polish spaces is a function of the first Baire class on the complement $X × Y \backslash M$ of a certain projectively meager set $M ⊂ X × Y$.